Dispute Resolution Due to Default Based on Contract Agreement: Case Study of PT. Serayu Putra Persada With CV. Mustika Karya Pratama - Perdana, Radiex Wisnu (UMPurwokerto Law Review, 2020)
Development is an effort to create the prosperity and welfare of the people. The stages of development work sometimes experience obstacles, both from human factors and other resources. Problems that can occur during the implementation of construction work include potential disputes, disagreements, differences in understanding, or disputes between parties involved in a construction agreement that will default. The method in this research uses the normative juridical method. The normative juridical method is carried out through literature studies examining mainly secondary data in statutory regulations, court decisions, agreements, contracts, other legal documents, research results, study results, and other references. The result of this research is the default made by CV. Mustika Karya Pratama in the form of not making payments so that PT. Serayu Putra Persada came to the office of CV. Mustika Karya Pratama to ensure the continuation of term payments. With these problems, it is hoped that the parties involved in this work can comply with and understand the legal rules that have been set. Keywords: Â Development, Agreement, Default.